2019
DOI: 10.1042/bsr20171307
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of cardiomyocytes in diabetic cardiomyopathy involves overexpression of glycogen synthase kinase-3β

Abstract: To evaluate the role of glycogen synthase kinase-3β (GSK-3β) in the apoptosis of cardiomyocytes in diabetic cardiomyopathy (DCM). Diabetes mellitus (DM) in rats was induced by intraperitoneal injection of 1% streptozotocin (STZ), and lithium chloride (LiCl) was used to decrease the expression of GSK-3β. Hematoxylin/eosin (HE) staining and the terminal deoxyribonucleotide transferase-mediated dUTP-digoxigenin nick end labeling (TUNEL) assay was conducted to evaluate the pathological injury and apoptosis of card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 31 publications
0
12
0
2
Order By: Relevance
“…It was suggested that suppressing expression of the lncRNA NKILA may inhibit the development of DC. 27 The apoptosis of cardiomyocytes under high-glucose conditions contributes to the pathogenesis of DC, 28 overexpression, as well as knockdown of the lncRNA NKILA accelerated and inhibited apoptotic cell death, respectively. 27 Compared with healthy subjects, patients with T2DM showed a more than fivefold increase in expression of the lncRNA NEAT1.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that suppressing expression of the lncRNA NKILA may inhibit the development of DC. 27 The apoptosis of cardiomyocytes under high-glucose conditions contributes to the pathogenesis of DC, 28 overexpression, as well as knockdown of the lncRNA NKILA accelerated and inhibited apoptotic cell death, respectively. 27 Compared with healthy subjects, patients with T2DM showed a more than fivefold increase in expression of the lncRNA NEAT1.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis of cardiomyocytes under a high-glucose environment contributes to the pathogenesis of DC (19), and inhibition of this pathophysiological process is considered to be a promising therapeutic target for DC (20). In the present study, it was illustrated that lncRNA NKILA overexpression and lncRNA NKILA knockdown accelerated and inhibited apoptotic cell death in cardiomyocytes under high-glucose treatment, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms responsible for the increased rates of apoptosis include increased production of ROS, endoplasmic reticulum stress, increased activation of the TGF-β1 signaling pathway, increased circulating inflammatory cytokines and chemokines, increased RAAS local activation, increased caspase activation, resistance to IGF-1 and altered expression of pro- and anti-apoptotic molecules [ 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. Mitochondrial oxidative stress was found to be alleviated by metallothionein treatment in streptozotocin-treated mice, attenuating cell death [ 106 ]. Increased expression of glucose-regulated protein 78 (Grp78) and caspase12 in diabetic heart indicates the activation of endoplasmic reticulum-stress response that leads to cell death via apoptosis.…”
Section: Involvement Of Mitochondria Dysfunction In Diabetic Cardimentioning
confidence: 99%
“…Glycogen synthase kinase-3 β (GSK-3 β) induces apoptosis via activation of the apoptosis-related protease-caspase family and B-cell lymphoma 2 associated x-protein (BAX) genes [ 106 ]. Xu et al [ 107 ] reported that metformin was able to restore autophagic activity and inhibit cardiomyocyte apoptosis via disruption of B-cell lymphoma 2 (Bcl-2) and Beclin-1 complex in diabetic heart tissue.…”
Section: Involvement Of Mitochondria Dysfunction In Diabetic Cardimentioning
confidence: 99%